Implementation of Complete Systematic Land Registration (PTSL) for Customary Land in Sorong Regency - Andi Sandi; Masrifatun Mahmudah (Faculty of Law, Universitas Muhammadiyah Sorong, 2024)
This research aims to analyze the implementation of the Complete Systematic Land Registration (PTSL) Program on customary land in Sorong Regency, West Papua, as well as the challenges faced by the local National Land Agency (BPN) in increasing public legal awareness of the importance of land registration. The research method used is empirical research method, which collects data through interviews, observation, and documentation. Primary data was obtained from interviews with indigenous people and the BPN, while secondary data came from relevant legal literature. The results show that the implementation of PTSL in Sorong Regency is still not optimal, especially in rural areas such as Wonosobo Village. Many indigenous people do not understand the benefits and objectives of land registration, so the program does not receive a positive response. This problem is exacerbated by geographical challenges, limited BPN human resources, and community distrust of the land certification process. As a result, many customary lands are unregistered and vulnerable to being taken by third parties, such as plantation companies, with minimal compensation. In conclusion, the implementation of PTSL in Sorong has not succeeded in achieving its goal of providing legal certainty and protection for customary landowners. Additional efforts are needed from BPN Sorong to improve equitable socialization and provide a clear understanding to the community on the importance of customary land registration as an effort to reduce potential land disputes in the future.